2003
DOI: 10.1007/s00466-003-0420-9
|View full text |Cite
|
Sign up to set email alerts
|

A mixed finite element formulation for timoshenko beam on winkler foundation

Abstract: A mixed formulation for Timoshenko beam element on Winkler foundation has been derived by defining the total curvature in terms of the bending moment and its second order derivation. Displacement and moment have been chosen as primary variables, while slope and first derivation of moment have been chosen as secondary variables. The behaviour matrix for Timoshenko beam element has been obtained in mixed form by using weak formulation with equilibrium and compatibility equations. The presented formulation makes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Reports of other approaches, such as relaxation techniques22, iterative methods23–26, integral transform techniques27, matrix method28–32, and initial condition methods33, can be found in the literature. Other recent developments included the Green's function approach34, 35, finite element methods36–39, and boundary integral equation methods40. In particular, Yin41, 42 has developed a Timoshenko beam model for the analysis of interaction action between a reinforced structure and the soil.…”
Section: Beams On An Elastic Foundationmentioning
confidence: 99%
“…Reports of other approaches, such as relaxation techniques22, iterative methods23–26, integral transform techniques27, matrix method28–32, and initial condition methods33, can be found in the literature. Other recent developments included the Green's function approach34, 35, finite element methods36–39, and boundary integral equation methods40. In particular, Yin41, 42 has developed a Timoshenko beam model for the analysis of interaction action between a reinforced structure and the soil.…”
Section: Beams On An Elastic Foundationmentioning
confidence: 99%
“…A discrete method such as the Finite Element Method (FEM) is the first to address the problem numerically [1][2][3]. The Differential Quadrature Method (DQM) is also employed for the solution to similar engineering problems involving beam vibrations and foundations [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhaohua and Cook [34] showed that in a certain case, only one beam-foundation element derived based on the exact displacement interpolation functions yielded results as precise as those obtained with eighty beam-foundation elements derived based on the assumed Hermite displacement interpolation functions. Due to some desirable features of the force method recognized in the framework of structural analysis [42,43], several researchers [15,44,45] have developed the beam-foundation elements based on mixed and force-based finite element formulations using the assumed displacement and force interpolation functions. Although a drastic improvement in the model accuracy was gained in these unconventional beam-foundation elements, an approximate nature was still inherent in their element stiffness matrices.…”
Section: Introductionmentioning
confidence: 99%